CAR-T: from bench to bedside - M. О. Popova; V. V. Markelov (Онкогематология)
In current immunotherapy, a promising direction is therapy using chimeric antigen receptor T cells (CAR-T). Among malignant hematological diseases, even at advanced stages and resistant/recurrent forms, the use of CAR-T demonstrates high efficiency. The observed clinical success in patients with hematologic malignancies not only determines the ever-increasing list of indications for the use of CAR-T in this group of patients, but also motivates the study of this treatment method in solid oncology and autoimmune diseases. This review examines the history of the emergence and development of CAR-T, the path from the idea of creation to registration to clinical use.